Presentation of a Case of Short Root Anomaly in an 11-Year-Old Child - Angeliki Sofia Trimeridou; Aristidis Arhakis; Konstantinos Arapostathis (Case Reports in Dentistry)
Short root anomaly (SRA) is a developmental anomaly in which the affected teeth present morphologically normal crowns and short, round roots. The exact cause of SRA is unknown. A case of an 11-year-old female patient with SRA is described. The patient presented short, round roots of all permanent teeth but first molars. Maxillary lateral incisors presented severe root resorption and mobility. Treatment plan included preservation of the maxillary lateral incisors by splinting them to their adjacent teeth using a stainless steel coaxial wire. A custom mouthguard for dental trauma protection was also constructed using a computer-aided design - computer-aided manufacturing (CAD–CAM) system in order to fabricate 3D-printed dental casts. At 2-year follow-up, the mobility of maxillary lateral incisors decreased, and the patient’s dentition remained stable. Considerations regarding differential diagnosis, orthodontic management, and treatment options after an eventual loss of teeth are thoroughly discussed.